Status dan Kedudukan Techplomacy dalam Hukum Internasional (Studi Terhadap TechAmbassador Negara Denmark) - Mahfyra Shalsabella Hamyda (Jurist-Diction, 2021)
AbstractThe world continues to develop, supported by unstoppable technological developments. Technology companies are taking an important role in significant technological developments. However, behind the technological developments pioneered by these technology companies, it is not balanced with the formation of fast and appropriate regulations. Until now, there is still a clear gap between the state government and technology companies. To solve this problem, Denmark became the first country to do techplomacy, represented by a TechAmbassador who in carrying out their duties using the global mandate method. TechAmbassador is in charge of bridging the government and technology companies. Techplomacy is the responsibility of the Danish Ministry of Foreign Affairs and in practice still uses the traditional diplomacy style. There are similarities and differences between techplomacy and diplomacy stipulated in the Vienna Convention 1961. Keywords: Diplomacy; Techplomacy; TechAmbassador; Vienna Convention 1961.AbstrakDunia terus berkembang didukung oleh perkembangan teknologi yang tidak dapat dibendung. Perusahaan teknologi mengambil peran penting dalam perkembangan teknologi yang signifikan. Namun, dibalik perkembanga teknologi yang dipelopori oleh perusahaan teknologi tersebut tidak diimbangi dengan pembentukan regulasi yang cepat dan sesuai. Hingga sampai sekarang, masih terlihat jelas jarak antara pemerintah negara dengan perusahaan teknologi. Untuk menyelesaikan persoalan tersebut, Denmark menjadi negara pertama yang melakukan techplomacy dengan diwakili dengan seorang TechAmbassador yang dalam melakukan tugasnya menggunakan cara mandate global. TechAmbassador bertugas untuk menjembatani antara pemerintah dengan perusahaan teknologi. Techplomacy menjadi tanggung jawab Kementerian Luar Negeri Denmark dan dalam praktiknya masih menggunakan gaya diplomasi tradisional. Ada persamaan dan perbedaan antara techplomacy dengan diplomasi yang diatur dalam Konvensi Wina 1961. Kata Kunci: Diplomasi; Techplomacy; TechAmbassador; Konvensi Wina 1961.